2022
DOI: 10.21203/rs.3.rs-1751258/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary Survey on the Health and Management Practices Among Small-scale Cage Tilapia Farmers on Lake Volta

Abstract: The study investigated the health and management strategies adopted by fish farmers on Lake Volta to control disease outbreaks. 30 fish farmers were randomly selected within stratum II of the Lake Volta and interviewed using semi-structured questionnaires and oral discussions to collect information on their knowledge, experiences and measures used in controlling the spread of fish diseases. Farmers face challenges including poor water quality and seed and incidence of diseases. 56% of farmers reported they hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Interestingly, findings from a quantitative study suggested that the Lake has a fairly good chemical health status (Tay, 2021). However, the results from a qualitative study corroborate the findings in this study, as water quality was purported to have aggravated disease incidences in farmed fish on the Lake (Abarike et al, 2022). The results in this study thus suggest the need to formulate testable hypothesis on specific water quality contaminants, such as herbicides and pesticides, as disclosed by the participants.…”
Section: Risk Factors Of Tilapia Mortalitiessupporting
confidence: 74%
“…Interestingly, findings from a quantitative study suggested that the Lake has a fairly good chemical health status (Tay, 2021). However, the results from a qualitative study corroborate the findings in this study, as water quality was purported to have aggravated disease incidences in farmed fish on the Lake (Abarike et al, 2022). The results in this study thus suggest the need to formulate testable hypothesis on specific water quality contaminants, such as herbicides and pesticides, as disclosed by the participants.…”
Section: Risk Factors Of Tilapia Mortalitiessupporting
confidence: 74%
“…Sampled cage farms in stratum II of the Volta Lake within the Akosombo Dam at 6°17′57.7″ N 0°03′19.6″ E is designated as upstream, through the area between the Akosombo Dam and Kpong Dam at 6°07′12.4″ N 0°07′31.4″ E is designated as midstream, and after the Kpong Dam at 6°06′02.3″ N 0°09′26.2″ E through to the Akuse area is designated as downstream. These demarcations are the original sections of the stratum II of the Volta Lake, which were the sampled areas for the study (Figure 12) [64].…”
Section: Study Areamentioning
confidence: 99%